Incidence of Hypocalcemia in Women Suffering from Preeclampsia - Madiha Haroon, Hina Zubair, Asma Qamar Mudassir, Saima Perveen, Aurooj Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To estimate the incidence of hypocalcemia in women suffering from preeclampsia. Study Design: Cross sectional study. Place and Duration of Study: Department of Obstetrics & Gynaecology, Pakistan Railway Hospital Rawalpindi from 1st July 2020 30th June 2021. Methodology: One hundred women with preeclampsia were suffering from high blood pressure and amenorrhea 32 weeks’ pregnant women with parity between 0-5 were enrolled. They were divided in two groups. Group A consisted of normal pregnant women while Group B consisted of pre-eclamptic pregnant women. Blood pressure was taken at three various times using a mercury based sphignomometer. Urine analysis was initially performed as a confirmation of preeclampsia. Serum Calcium levels were determined through calorimetric method using Human Diagnostic kits (Germany). Results: The study highlighted the fact that majority of the pre-eclamptic women such as 54% were educated. There was a significant difference in primigravida of group A and Group B with p value <0.05. Conclusion: Significant association was found between hypocalcemia and preeclampsia among pregnant women.